2016
DOI: 10.1111/ijac.12620
|View full text |Cite
|
Sign up to set email alerts
|

Moisture sensing studies of CuO‐ZnO nanocomposites

Abstract: This paper reports the characterization and humidity sensing studies of CuO–ZnO nanocomposites prepared by solid‐state reaction method. The electrical resistance of nanocomposites continuously decreased when relative humidity (RH) was increased from 10% to 95% RH. Nanocomposites with 1 wt% of CuO in ZnO showed the best results with a sensitivity of 29.95 MΩ/%RH. This sample also showed low hysteresis and high reproducibility. This sample had an average particle and crystallite size of 200 nm and 70 nm, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition to organic polymers, the coupling of semiconducting metal oxides ZnO [83,84], TiO 2 [85], SnO 2 [103], In 2 O 3 [104], and Fe 3 O 4 and Cu 2 O [81] into copper oxide can also significantly enhances its sensing performance. After careful summary investigations, we found that the resulting nanocomposites after coupling significantly improved the humidity-sensing behavior.…”
Section: Metal Oxide Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to organic polymers, the coupling of semiconducting metal oxides ZnO [83,84], TiO 2 [85], SnO 2 [103], In 2 O 3 [104], and Fe 3 O 4 and Cu 2 O [81] into copper oxide can also significantly enhances its sensing performance. After careful summary investigations, we found that the resulting nanocomposites after coupling significantly improved the humidity-sensing behavior.…”
Section: Metal Oxide Dopingmentioning
confidence: 99%
“…Generally, the combination of narrow bandgap semiconductor and wide bandgap semiconductor will improve its sensing performance. Rajput et al [83] reported the preparation of CuO-ZnO nanocomposites. It was found that between 10% and 95%RH, with the increase of copper oxide content, the resistance of the nanocomposite changed more significantly, and its humidity-sensitive performance and sensitivity were better In another experiment, Zainelabdin and colleagues [84] reported the preparation of copper oxide nanomaterials with special morphologies on ZnO nanorods (NRs) by a hydrothermal method.…”
Section: Metal Oxide Dopingmentioning
confidence: 99%
“…When Cu's behaviour as an acceptor impurity in n-type ZnO was discovered, it was decided to introduce copper oxide because it significantly changed the electrical and optical characteristics of ZnO [5][6][7]. Rajput et al [8] have studied and suggested that the humidity sensitivity of the nanocomposite CuO-ZnO prepared by the solid-state reaction route increased as the doping % increased. By using aqueous fruit extracts of Myristica fragrans, Faisal et al [9] have created bioaumented zinc oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%